Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants

Impact of fly ash impurity on the hydrate-based gas separation process for carbon dioxide capture from a flue gas mixture - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2014)
The hydrate-based gas separation (HBGS) process for gas mixtures of CO2 + N-2 (flue gas) and CO2 + H-2 (fuel gas) has proven to be very efficient and highly selective for CO2 capture. In addition to CO2 and N-2, flue gas from coal-based thermal power stations can contain impurities such as nitrogen oxides (NOx), sulfur oxides (SOx), and fly ash. In this work, the impact of fly ash on the HBGS process efficiency was investigated. Tetrahydrofuran (THF, 1 mol %) was used as a thermodynamic promoter, and sodium dodecyl sulfate (SDS) and sodium dodecyl benzenesulfonate (SDBS) (anionic surfactants) were used as kinetic promoters. Whereas the use of THF in the HBGS process reduces the operating pressure significantly, both SDS and SDBS were found to enhance the rate of hydrate formation. It was observed that the hydrate equilibrium conditions did not change in the presence of fly ash. However, the presence of fly ash enhanced the separation efficiency of the HBGS process by reducing the induction time and increasing the kinetics of hydrate formation. Therefore, the presence of fly ash in a flue gas mixture is not detrimental to the HBGS process, which is a positive factor for the capture and geological sequestration of CO2 in the form of gas hydrates.

Influence of low-dosage hydrate inhibitors on methane clathrate hydrate formation and dissociation kinetics - Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (Energy Technology, 2015)
This work investigates the effect of low-dosage hydrate inhibitors (LDHIs) on methane hydrate formation and dissociation. The hydrate inhibitors used in this study were the sodium salt of polyacrylic acid, a polysaccharide chitosan, and the linear sulfated polysaccharide i-carrageenan; the inhibiting behavior of these additives were compared with that of the commonly used hydrate inhibitor polyvinylpyrrolidone for methane hydrate formation. A LDHI concentration of 1wt% was found to increase the induction time relative to that at a LDHI concentration of 0.1wt%. Chitosan was found to be better than the others in reducing nucleation and the growth rate of the hydrate at a concentration of 1wt%. At a lower concentration of 0.1wt%, nucleation inhibition was minimal, however, growth inhibition was significant. The effect of these inhibitors on the decomposition rate of the hydrate was also studied, and the decomposition kinetics at a constant driving force in excess of three-phase equilibrium is reported.
Keywords: gas uptake; hydrates; inhibitors; kinetics; thermal stimulation

Impact of H2S impurity on carbon dioxide hydrate formation kinetics in fixed bed arrangements - Kumar, Asheesh; Sakpal, Tushar; Bhattacharjee, Gaurav; Kumar, Anupam; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2016)
In the present work, a combination of silica sand and metallic sheets as a fixed bed media was used for carbon dioxide hydrate formation studies. Two metallic sheets, aluminum and brass, were incorporated into the fixed bed of silica sand to enhance heat transfer properties of the bed. The results obtained from this arrangement of metal sheets were compared with those obtained with a pure silica sand system. Both brass and aluminum systems were found to be good candidates to enhance gas hydrate formation kinetics compared to simply a sand system. Production of fuel gas from coal often contains a toxic gas, hydrogen sulfide (H2S). For the first time, the effect of H2S on the formation kinetics of CO2 + H-2 + H2S hydrates has been studied. It was observed that the presence of H2S does not affect the hydrate formation kinetics and total gas uptake in the presence of H2S is either as good as CO2 + H-2 hydrate or better. However, H2S impurity in the fuel gas mixture shows a corrosive effect on silica sand media.